Metal−Organic Frameworks for Environmental Sensing - S. Kumar, Smita, editor 645616; Ghosh, Pooja, editor 645609; Singh, Lakhveer , editor 645611; ACS Publications (Online service) 645714 (Washington, DC : American Chemical Society, 2021)
"Quantifying Contaminants with MOFs. Metal-organic frameworks (MOFs) have emerged as highly customizable catalysts based on their unique features. Recent studies have developed specific MOFs for many applications. As part of a three-volume set (1393-1395), this volume provides an overview on MOFs used in environmental sensing, including synthesis, characterization, and examples of applications. Materials scientists, chemical engineers, and environmental scientists will find this work useful, as will students learning about this active area of research."-- Provided by publisher.